Depression, anxiety, and stress in health professionals working during the covid-19 pandemic in Peru: An analytical cross-sectional study - Quispe-Sancho, Alan (2021)
Objective: To determine the association between depression, anxiety, and stress according to sociodemographic and occupational factors in Peruvian health professionals during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Cross-sectional analytical and multicentre study, based on a virtual survey sent to Peruvian health personnel (from the 25 Peruvian regions) working during the COVID-19 pandemic. The three dependent variables (depression, anxiety, and stress) were measured with the Depression, Anxiety, and Stress Scale -21 (DASS-21) (Cronbach’s Alpha: 0.93) and compared with sociodemographic and occupational variables. P-values were obtained through generalized linear models, adjusted for each location where the survey was sent. Results: Of the 550 participants, 2%, 13%, and 3% of them had severe or very severe depression, anxiety, and stress, respectively. In the multivariate analysis, we observed that professionals with a greater number of children had a lower frequency of severe depression (adjusted prevalence ratio (aPR): 0.37; 95% confidence interval (CI): 0.17-0.79; p = 0.010). In addition, physicians had a lower frequency of severe anxiety (aPR: 0.37; 95% CI: 0.18-0.75; p = 0.036), and professionals who lived in the Central region (aPR: 0.50; 95% CI: 0.25-0.97; p = 0.042) and in the South of the country (aPR: 0.37; 95% CI: 0.19-0.71; p = 0.003) had lower anxiety levels compared to those in the Northern region. With regard to severe stress, those who lived in the Central (aPR: 0.15; 95% CI: 0.03-0.75; p = 0.021) and South regions (aPR: 0.19; 95% CI: 0.04-0.79; p = 0.011) had lower stress levels. Conclusion: There were significant percentages of deteriorating mental health in Peruvian health professionals during the pandemic, which may have negative repercussions in the short-, medium-, and long-term. In this sense, additional governmental actions should be necessary to provide specific psychological and psychiatric support programs to these workers.